Baroque Seville : sacred art in a century of crisis - Wunder, Amanda Jaye, 1972- (The Pennsylvania State University Press, 2017)
"Explores the making of seventeenth-century Seville's greatest Baroque monuments. Conceived as a spiritual solution to Seville's problems, these works had a profound real-world effect on the city in crisis. Examines Baroque art as a collaborative process involving not only painters but altarpiece designers, plaster carvers, embroiderers, printmakers, and authors"